The Redesign of E-Investigation Management Implementation in Brebes Police Department Criminal Investigation Unit for Transparent and Equitable Law Enforcement - Ayanda, Muhammad Alkeizar (Advances in Police Science Research Journal, 2024)
PRESISI is a catalyst for Indonesia National Police in optimizing the organization and creating transparent justice in adaptive law enforcement. Innovative thinking in the digital era. One of the programmes developed to support these efforts is E-Investigation Management. However, this programme could have been more optimal in its implementation. Brebes Police Department experienced a similar problem. There are still many problems, from resources to operations. This is a vulnerable element considering that the programme will be the vehicle for supplying the National Criminality Information Centre. Therefore, this study aims to describe the redesign of implementing the E-Investigation Management in the Brebes Police Criminal Investigation Unit for transparent and equitable law enforcement. This research is field research using a descriptive approach. The research location is located at the Brebes Police Department Headquarters with a focus on the Criminal Investigation Unit. The technique of determining informants uses purposive sampling, where informants are selected because they have mastered the management of E-Investigation Management. Primary data sources used came from interviews and observations. Secondary data comprised official documents, previous research, and internet searches on E-Investigation Management. To maintain data validity, triangulation of sources and methods was used. Then, data analysis consists of data collection, reduction, presentation, and conclusion drawing. The results of this study indicate that the E-Investigation Management of the Brebes Police Department Criminal Investigation Unit needs to run according to its purpose. Administration of investigations is still carried out conventionally, so E-Investigation Management has yet to be used in filing. This is due to the condition of human resources, which still need to be competent in digital-based filing. In addition, the application that has yet to be developed has different features between output investigation administration files and its facts. Various analytical services have also yet to be used optimally in decision-making. Therefore, a redesign of EMP management is urgently needed. This effort is supported by reorganized planning, organization, deployment, and supervision based on the SEInvestigation Management Standard Operational Procedure.